Defending poetry art and ethics in Joseph Brodsky, Seamus Heaney, and Geoffrey Hill - Williams, David-Antoine, 1978- (Oxford : Oxford University Press, 2010)
Through readings of the poems & prose essays of Joseph Brodsky Seamus Heaney, & Geoffrey Hill, 'Defending Poetry' makes a timely intervention in current debates about literature's ethics, arguing that any ethics of literature ought to take into account not only poetry, but also the writings of poets on the value of poetry.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Brodsky, Joseph, -- 1940-1996 -- Criticism and interpretation; Heaney, Seamus, -- 1939- -- Criticism and interpretation; Hill, Geoffrey -- Criticism and interpretation; Ethics in literature